HAZARD IDENTIFICATION AND RISK ASSESSMENT IN BOILER DIVISION USING HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL (HIRARC) - Supriyadi Supriyadi; Fauzi Ramdan (Universitas Darussalam Gontor, 2017)
Every workplaces have always risk of accidents which need efforts to prevention and control it doesnot happen. Occupational risks hazard identification is an early step that must be considered by the company. The purpose of the study is to determine the type of hazard, risk assessments based on sources hazard and risk assessment based on the types of hazards in the boiler division. Data collection on the identification and assessment of risks analyzed by HIRARC, evaluated and find the better solution to determined and control hazards in the workplace so that the workplace safely. The result showed the sources of the dangers are charcoal dust, sparks, heat radiation, falls, pinched, charcoal sprinkle, noise, electric high pressure, explosion, fire, hot material, exposed to chemicals, inhaling chemicals, steam, leaks in drum steam, hot water, excess gas pressure and embers. The rate based on hazardsources in the boiler division has Extrim Risk levels (8%), High Risk (14%), Moderate Risk (35%) and Low Risk (43%). Risk assessment based on the type of hazard in the boiler division have risk levels ranging from high to the lowest score is the danger of Mechanical (25%), Electrical hazard (10%), chemical hazards (6%) and physical hazards (59%). Keywords: Hazard Identification; Work safety; Risks and HIRARC